Effect of pH Variation on Solubility of Seed Proteins in Some New and Hybrid Varieties of Legume and Oil Seeds - Thakur, Shweta; Shrivastava, S.K.; Shrivastava, Manjul (Asian Journal of Chemistry, 2010)
The effect of pH variation (ranging from 0.5-13.5) on the solubility of seed protein of seven varieties of leguminous and oil seeds viz., Glycine max (NRC-37), Vigna radiata (LGG-460), Phaseolus mungo (LBG-20), Cicer arietinum (JG-130), Lens esculenta (JL-3), Sesamum indicum (JTS-8) and Guizotia abyssinic (JNC-6). All seven varieties exhibited characteristic curves towards maximum solubility ranging from 12.0 to 12.5 pH.